2021
DOI: 10.3390/electronics10232997
|View full text |Cite
|
Sign up to set email alerts
|

Open Data Based Machine Learning Applications in Smart Cities: A Systematic Literature Review

Abstract: Machine learning (ML) has already gained the attention of the researchers involved in smart city (SC) initiatives, along with other advanced technologies such as IoT, big data, cloud computing, or analytics. In this context, researchers also realized that data can help in making the SC happen but also, the open data movement has encouraged more research works using machine learning. Based on this line of reasoning, the aim of this paper is to conduct a systematic literature review to investigate open data-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
0
10
0
4
Order By: Relevance
“…However, it is less frequent because companies refuse to freely share their data and to assume the costs related to the publication process [7]. The research conducted by Hurbean et al [8] proposes the Internet of Things (IOT), and Machine Learning (ML) in combination with LOD platforms as the key elements for building smart city applications.…”
Section: Data Are One Of the Most Valuablementioning
confidence: 99%
See 2 more Smart Citations
“…However, it is less frequent because companies refuse to freely share their data and to assume the costs related to the publication process [7]. The research conducted by Hurbean et al [8] proposes the Internet of Things (IOT), and Machine Learning (ML) in combination with LOD platforms as the key elements for building smart city applications.…”
Section: Data Are One Of the Most Valuablementioning
confidence: 99%
“…In the introduction, we mentioned that LOD supports the digital transformation of cities by providing a mechanism to publish a consume source of information in a free and understandable way [2], [9], [8]. In the LOD ecosystem, there are two main stakeholders: data publishers (providers) and data users (consumers).…”
Section: Open Data In Smart City Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The availability of open data has led to increased research using artificial intelligence for various applications. Furthermore, open data has been recognized as a catalyst for machine learning (ML), particularly in air pollution prediction, traffic forecasting, urban design, and transport features analysis [12]. It has facilitated knowledge discovery by making data findable, accessible, interoperable, and reusable, as per the FAIR Data Principles [13].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the housing supply in smart cities is influenced by a complex interplay of various factors, including financing costs, construction costs, vacancy rates, and regulatory constraints [26]. Studies have shown that financing costs, such as interest rates, have a negative effect on housing starts-a crucial economic indicator, as it reflects the health and direction of the housing market and, by extension, provides insights into broader economic conditions [12]. Similarly, construction costs, including material and wage costs, can also affect the housing supply, although the results are inconclusive in some cases [19].…”
Section: Introductionmentioning
confidence: 99%